Creating dynamic UIs with Android fragments : create engaging apps with fragments to provide a rich user interface that dynamically adapts to the individual characteristics of your customers' tablets and smartphones /: create engaging apps with fragments to provide a rich user interface that dynamically adapts to the individual characteristics of your customers' tablets and smartphones. (2016) - Wilson, Jim
No abstract available